Representations : images of the world in Ciceronian oratory - Vasaly, Ann.; California Digital Library. eScholarship (Berkeley, Calif. : University of California Press, 1993)
Ann Vasaly introduces representation theory into the study of Ciceronian persuasion and contends that an understanding of milieu--social, political, topographical--is crucial to understanding Ciceronian oratory. As a genre uniquely dependent on an immediate interaction between author and audience, ancient oratory becomes performance art. Vasaly investigates the way Cicero represented the contemporary physical world--places, topography, and monuments, both those seen and those merely mentioned--to his listeners and demonstrates how he used these representations to persuade. Her exceptionally well-written study deftly recaptures the immediacy of Cicero's oratory and makes a trenchant contribution to an important new area of inquiry in Classical Studies.
Ambiance, rhetoric and the meaning of things -- Transforming the visible: in Catilinam 1 and 3 -- Signa and signifiers: a world created -- Ethos and Locus: ancient perspectives -- Place and commonplace: country and city -- Ethnic personae.
Includes bibliographical references (pages 261-276) and indexes.
Print version record.
In English.
JSTOR
Keywords: Cicero, Marcus Tullius; Speeches (Cicero, Marcus Tullius); Cicero, Marcus Tullius -- v106-v43; Cicero, Marcus Tullius -- v106-v43; Bibel; Cicéron (0106-0043 av. J.-C.).; Cicero, Marcus Tullius; Orationes; Rhetorica; Speeches, addresses, etc., Latin -- History and criticism; Mimesis in literature; Rome -- In literature; Oratory, Ancient; Discours latins -- Histoire et critique; Mimêsis dans la littérature.; Éloquence antique; FOREIGN LANGUAGE STUDY -- Latin; Literature; Mimesis in literature; Oratory, Ancient; Speeches, addresses, etc., Latin; Rome (Empire); Rede; Zeithintergrund; Weltbild; Redes; Publiek; Wereldbeeld; Rhétorique antique; ambiance; ancient literature; ancient perspectives; cicero; ciceronian oratory; ciceronian persuasion; ciceronian studies; classical literature; classical studies; ethnic; ethos and locus; in catilinam; literary theory; meaning of things; milieu; monuments; oral communication; oratory; performance art; persuade; persuasion; physical world; places; political structures; public presentation; raw material; representation theory; rhetoric; signa; social structures; topographical structures